1
$\begingroup$

Let $C$ be a non-empty convex subset of $\mathbb{R}^n$. We say that $x\in C$ is a extreme point of $C$ if for every $z,y\in C$ and $t\in [0,1]$ such that $x=ty+(1-t)z$ we have $x=z$ or $x=y$. Or equivalently, if for every $z,y\in C$ and $t\in (0,1)$ such that $x=ty+(1-t)z$ we have $x=z=y$.

I want to prove the following:

If $x$ is a extreme point of $C$, then for every $x_1,...,x_m\in C$ and $\lambda _1,...,\lambda _m >0$ such that $x=\lambda _1x_1+...+\lambda _mx_m$ we have $x=x_i$ for some $i$.

Any hint? Thanks.

$\endgroup$
  • 1
    $\begingroup$ That's false like that. Take $C=[0,1]$. Then $1=2\cdot\frac{1}{4}+1\cdot\frac{1}{2}$. It is true if you add the condition $\sum_{j=1}^m\lambda_j=1$. And then it follows from a straightforward induction on $m$. $\endgroup$ – Julien May 4 '13 at 22:12
  • $\begingroup$ Thank you. But how to manipulate the expression $x = \displaystyle\sum_{j=1}^{m+1}\lambda _jx_j$ if $\displaystyle\sum_{j=1}^{m+1}\lambda _j = 1$ to apply induction? $\endgroup$ – user73564 May 4 '13 at 22:45
  • $\begingroup$ If $\lambda_{m+1}=1$, you're done. If not $x=(1-\lambda_{m+1})y+\lambda_{m+1}x_{m+1}$ with $y=\sum_{j=1}^m\frac{\lambda_j}{1-\lambda_{m+1}}x_j$. $\endgroup$ – Julien May 4 '13 at 22:50
  • $\begingroup$ You can write the answer and accept it, if you want. Note that the case $\lambda_{m+1}=1$ I considered was pointless. This can't happen, when you suppose $\lambda_j>0$ for every $j$ and $\sum \lambda_j=1$. $\endgroup$ – Julien May 4 '13 at 23:01
  • $\begingroup$ Maybe it is another mistake. I think it must be $\lambda _j\ge 0$. If we put $\lambda _j > 0$, the conclusion would be $x=x_1=...=x_m$ instead $x=x_i$ for some i. What do you think? $\endgroup$ – user73564 May 4 '13 at 23:18
1
$\begingroup$

Compiling the comments into a CW:

  1. It must be assumed that $\sum_{j=1}^m \lambda_j =1$
  2. The case $m=2$ is the definition of an extreme point.
  3. For $m>2$ use induction: since $x=(1-\lambda_m)y+\lambda_m x_m$ with $y=\sum_{j=1}^{m-1}\frac{\lambda_j}{1-\lambda_m}x_j$, it follows that $x_m=x$ and $y=x$. Apply the inductive hypothesis to $y$.
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.